Associated Valvular Heart Diseases among ASD Patients Undergoing Surgical Repair (Journal of Current and Advance Medical Research, 2018)
Background: Congenital heart diseases (CHD) are one of the most common developmental errors in humans.Objectives: The purpose of the present study was to see the frequencies of various types of atrial septal defect (ASD) and associated cardiovascular disorders in patients undergoing surgical repair.Methodology: This cross-sectional study was conducted on patients undergoing surgical repair at the National Institute of Cardiovascular Diseases (NICVD) or the National Heart Foundation and Research Institute (NHF & RI) in Dhaka, during the period of July, 2010 to June, 2011. Patients presented with ASD at any age of both sexes were selected as study population. Diagnoses were revealed with echocardiography and confirmed preoperatively by registered cardiac surgeons.Results: The morphological types of ASD were ostium secundum type in 96% cases and sinus venosus type in 4% cases. Atrial septal defects were either small or larger defects associated with pulmonary hypertension in 38 (76%) cases, varying degree of tricuspid regurgitation was seen in 33 (66%) patients and dilated pulmonary artery was noted in 24 (48%) cases. Ventricular septal defect in 4 (8%) cases, tricuspid atresia in 2 (4%) cases and mitral valve prolapse in 6 (12%) cases were also observed.Conclusions: Ostium secundum type of ASD is found to be the commonest type of ASDJournal of Current and Advance Medical Research 2018;5(2):60-63